Insulin Resistance and Cancer-Specific and All-Cause Mortality in Postmenopausal Women: The Women's Health Initiative. (26th April 2019) - Pan, Kathy; Nelson, Rebecca A; Wactawski-Wende, Jean; Lee, Delphine J; Manson, JoAnn E; Aragaki, Aaron K; Mortimer, Joanne E; Phillips, Lawrence S; Rohan, Thomas; Ho, Gloria Y F; Saquib, Nazmus; Shadyab, Aladdin H; et al.
Abstract: Background: Insulin resistance has been proposed as a mediator of the increased cancer incidence and mortality associated with obesity. However, prior studies included limited cancer deaths and had inconsistent findings. Therefore, we evaluated insulin resistance and cancer-specific and all-cause mortality in postmenopausal women participating in the Women's Health Initiative (WHI). Methods: Eligible were a subsample of 22 837 WHI participants aged 50–79 years enrolled at 40 US clinical centers from 1993 to 1998 who had baseline fasting glucose and insulin levels. Baseline insulin resistance was measured by the homeostasis model assessment of insulin resistance (HOMA-IR). Cancers were verified by central medical record review and deaths verified by medical record and death certificate review enhanced by National Death Index queries. Cox proportional hazards regression models were used to calculate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for cancer-specific and all-cause mortality. All statistical tests were two-sided. Results: During a median of 18.9 years of follow-up, 1820 cancer deaths and 7415 total deaths occurred. Higher HOMA-IR quartile was associated with higher cancer-specific mortality (Q4 vs Q1, HR = 1.26, 95% CI = 1.09 to 1.47; P trend = .003) and all-cause mortality (Q4 vs Q1, HR = 1.63, 95% CI = 1.51 to 1.76; P trend < .001). A sensitivity analysis for diabetes status did not change findings. Among women with body mass index less than 25 kg/m 2, higher HOMA-IR quartile was associated with higher cancer mortality (Fine and Gray, P  = .004). Conclusions: High insulin resistance, as measured by HOMA-IR, identifies postmenopausal women at higher risk for cancer-specific and all-cause mortality who could potentially benefit from early intervention.